Marriage does not relate to major histocompatibility complex: a genetic analysis based on 3691 couples - Croy, Ilona; Ritschel, Gerhard; Kreßner-Kiel, Denise; Schäfer, Laura; Hummel, Thomas; Havlíček, Jan; Sauter, Jürgen; Ehninger, Gerhard; Schmidt, Alexander H (Proceedings. Biological sciences, 2020)
Optimization of chances for healthy offspring is thought to be one of the factors driving mate choice and compatibility of the major histocompatibility complex (MHC) is assumed to determine the offspring's fitness. While humans have been claimed to be able to perceive information of MHC compatibility via the olfactory channel, it remains unknown whether humans use such information for mate choice. By investigation of 3691 married couples, we observed that the high polymorphism of MHC leads to a low chance for homozygous offspring. MHC similarity between couples did not differ from chance, we hence observed no MHC effect in married couples. Hormonal contraception at the time of relationship initiation had no significant effect towards enhanced similarity. A low variety of alleles within a postcode area led to a higher likelihood of homozygous offspring. Based on this data, we conclude that there is no pattern of MHC dis-assortative mating in a genetically diverse Western society. We discuss the question of olfactory mate preference, in-group mating bias and the high polymorphism as potential explanations.
Keywords: manželství; Animals; lidé; HLA; mate choice; hlavní histokompatibilní komplex; Major Histocompatibility Complex; Marriage; Humans; Reproduction; assortative mating; rozmnožování; zvířata; mužské pohlaví; Male; human; ženské pohlaví; Female